Transforming growth factor-β(1) hyperexpression in African-American hypertensives: A novel mediator of hypertension and/or target organ damage - Suthanthiran, Manikkam (The National Academy of Sciences, 2000)
Hypertension, a remediable risk factor for stroke, cardiovascular disease, and renal failure, affects 50 million individuals in the United States alone. African Americans (blacks) have a higher incidence and prevalence of hypertension and hypertension-associated target organ damage compared with Caucasian Americans (whites). Herein, we explored the hypotheses that transforming growth factor-β(1) (TGF-β(1)) is hyperexpressed in hypertensives compared with normotensives and that TGF-β(1) overexpression is more frequent in blacks compared with whites. These hypotheses were stimulated by our recent demonstration that TGF-β(1) is hyperexpressed in blacks with end-stage renal disease compared with white end-stage renal disease patients and by the biological attributes of TGF-β(1), which include induction of endothelin-1 expression, stimulation of renin release, and promotion of vascular and renal disease when TGF-β(1) is produced in excess. TGF-β(1) profiles were determined in black and white hypertensive subjects and normotensive controls and included circulating protein concentrations, mRNA steady-state levels, and codon 10 genotype. Our investigation demonstrated that TGF-β(1) protein levels are highest in black hypertensives, and TGF-β(1) protein as well as TGF-β(1) mRNA levels are higher in hypertensives compared with normotensives. The proline allele at codon 10 (Pro(10)) was more frequent in blacks compared with whites, and its presence was associated with higher levels of TGF-β(1) mRNA and protein. Our findings support the idea that TGF-β(1) hyperexpression is a risk factor for hypertension and hypertensive complications and provides a mechanism for the excess burden of hypertension in blacks.